Characterization of the Human Blood Virome in Iranian Multiple Transfused Patients - Marijn Thijssen; Gholamreza Khamisipour; Mohammad Maleki; Timothy Devos; Guangdi Li; Marc Van Ranst; Jelle Matthijnssens; Mahmoud Reza Pourkarim (Viruses, 2023)
Blood transfusion safety is an essential element of public health. Current blood screening strategies rely on targeted techniques that could miss unknown or unexpected pathogens. Recent studies have demonstrated the presence of a viral community (virobiota/virome) in the blood of healthy individuals. Here, we characterized the blood virome in patients frequently exposed to blood transfusion by using Illumina metagenomic sequencing. The virome of these patients was compared to viruses present in healthy blood donors. A total number of 155 beta-thalassemia, 149 hemodialysis, and 100 healthy blood donors were pooled with five samples per pool. Members of the Anelloviridae and Flaviviridae family were most frequently observed. Interestingly, samples of healthy blood donors harbored traces of potentially pathogenic viruses, including adeno-, rota-, and Merkel cell polyomavirus. Viruses of the Anelloviridae family were most abundant in the blood of hemodialysis patients and displayed a higher anellovirus richness. Pegiviruses (Flaviviridae) were only observed in patient populations. An overall trend of higher eukaryotic read abundance in both patient groups was observed. This might be associated with increased exposure through blood transfusion. Overall, the findings in this study demonstrated the presence of various viruses in the blood of Iranian multiple-transfused patients and healthy blood donors.